2018
DOI: 10.30822/artk.v2i1.139
|View full text |Cite
|
Sign up to set email alerts
|

KAJIAN KEBETAHAN MAHASISWA DALAM LINGKUNGAN KAMPUS Studi Kasus: Kampus ITSB - Cikarang

Abstract: Dalam kesehariannya manusia melakukan interaksi dengan ruang dan lingkungan. Faktor fisik dan non fisik dari sebuah ruang akan mempengaruhi perasaan dan pengalaman seseorang berada di dalamnya. Kondisi ruang yang baik akan membuat seseorang merasa betah, sedangkan kondisi ruang yang tidak baik akan membuat seseorang merasa tidak betah. Lingkungan kampus ITSB merupakan salah satu fasilitas akademik yang di dalamnya digunakan oleh beberapa pengguna, yaitu mahasiswa, dosen, staf dan lainnya. Di dalamnya sangat me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, in Indonesia, students feel that radicalism is a real threat that can change a person's mindset. This context is even more worrying when the release of Setara Institute states that one of the campuses being studied at this time, UIN Bandung is one of the campuses with the highest level of intolerance in Indonesia (Satria, 2019). As a result, an attitude of caution is formed in responding to every movement of campus organizations, especially external ones.…”
Section: Student Efforts To Fortify Themselves From Radicalismmentioning
confidence: 99%
“…For example, in Indonesia, students feel that radicalism is a real threat that can change a person's mindset. This context is even more worrying when the release of Setara Institute states that one of the campuses being studied at this time, UIN Bandung is one of the campuses with the highest level of intolerance in Indonesia (Satria, 2019). As a result, an attitude of caution is formed in responding to every movement of campus organizations, especially external ones.…”
Section: Student Efforts To Fortify Themselves From Radicalismmentioning
confidence: 99%
“…Willingness to stay according to Rachman & Kusuma (2014) is a psychological condition where a person feels comfortable so he feels happy to stay for a long time in a place [10]. Satriaji (2017), when studying student willingness to stay on a campus, concluded that students' willingness to stay on the campus can be influenced by three factors, namely social interaction, the environment and physical facilities, and the activities undertaken [11]. The environment and physical facilities are the main factor affecting student welfare.…”
Section: Introductionmentioning
confidence: 99%